2021
DOI: 10.1186/s12862-021-01750-8
|View full text |Cite|
|
Sign up to set email alerts
|

Evolutionary pattern of karyotypes and meiosis in pholcid spiders (Araneae: Pholcidae): implications for reconstructing chromosome evolution of araneomorph spiders

Abstract: Background Despite progress in genomic analysis of spiders, their chromosome evolution is not satisfactorily understood. Most information on spider chromosomes concerns the most diversified clade, entelegyne araneomorphs. Other clades are far less studied. Our study focused on haplogyne araneomorphs, which are remarkable for their unusual sex chromosome systems and for the co-evolution of sex chromosomes and nucleolus organizer regions (NORs); some haplogynes exhibit holokinetic chromosomes. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(84 citation statements)
references
References 71 publications
(178 reference statements)
7
77
0
Order By: Relevance
“…The supposed stability of number and localization of NORs in spiders has knocked down with the increase of cytogenetic studies. In an analysis of NORs in 30 Pholcidae spiders, Ávila Herrera et al (2021) revealed a great diversity of number of this site, which can occur in autosomes and/or X sex chromosome. The results obtained herein using FISH with rDNA probe only in three Sicarius species revealed the presence of ribosomal cistrons in autosomes (S. ornatus and S. tropicus) and X 1 sex chromosome (S. cariri).…”
Section: Discussionmentioning
confidence: 99%
“…The supposed stability of number and localization of NORs in spiders has knocked down with the increase of cytogenetic studies. In an analysis of NORs in 30 Pholcidae spiders, Ávila Herrera et al (2021) revealed a great diversity of number of this site, which can occur in autosomes and/or X sex chromosome. The results obtained herein using FISH with rDNA probe only in three Sicarius species revealed the presence of ribosomal cistrons in autosomes (S. ornatus and S. tropicus) and X 1 sex chromosome (S. cariri).…”
Section: Discussionmentioning
confidence: 99%
“…Mapping of this cluster often revealed a single NOR site, which is probably an ancestral pattern in arachnids [36]. The number of NOR/rDNA loci has increased in some arachnid clades during their evolution [76,77,81,87]. In haplogyne spiders, these loci are also frequently placed on sex chromosomes [77,90].…”
Section: Distribution Of Rdna and Telomeric Sequencesmentioning
confidence: 98%
“…The major rDNA cluster (45S rDNA) is by far the most utilized molecular chromosomal marker across diverse eukaryotic organisms, and especially in non-model groups [72][73][74]. The major rDNA cluster visualized either by 18S or 28S rDNA probes has already been localized in some spiders [36,46,73,[75][76][77], scorpions [45,76,[78][79][80][81][82], pseudoscorpions [83], harvestmen [84][85][86][87], ticks [73,88,89], and an amblypygid [18]. Mapping of this cluster often revealed a single NOR site, which is probably an ancestral pattern in arachnids [36].…”
Section: Distribution Of Rdna and Telomeric Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…snetsingeri to compare with other Atypus species, along with observations on habitat associations and natural history. Data on karyotype [e.g., 27 , 28 ] and genetic barcode are frequently used to reconstruct phylogeny and evolutionary history of taxa including spiders.…”
Section: Introductionmentioning
confidence: 99%